1975
DOI: 10.4141/cjps75-075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Population and Row Spacing on Sunflower Agronomy

Abstract: The plots were harvested with a combine and the yield/ha was calculated; 1,000-seed weights were obtained and samples were analyzed for oil content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 1 publication
1
17
1
Order By: Relevance
“…However, in Minnesota an increase in plant population from 37 000 to 86 000 plants/ha increased yield at only one of two locations (Robinson, 1973). At Swift Current, Saskatchewan, yields of sunflower were similar across plant populations from 25 000 to 75 000/ha, but increased at 125 000 plants/ha (Vijayalakshmi et al, 1975). In our study, the differences in seed yield were not significant on a per-hectare basis, possibly because planting density did not vary as much as in previous studies where it varied by a factor of two or more.…”
Section: Source Of Variationcontrasting
confidence: 48%
“…However, in Minnesota an increase in plant population from 37 000 to 86 000 plants/ha increased yield at only one of two locations (Robinson, 1973). At Swift Current, Saskatchewan, yields of sunflower were similar across plant populations from 25 000 to 75 000/ha, but increased at 125 000 plants/ha (Vijayalakshmi et al, 1975). In our study, the differences in seed yield were not significant on a per-hectare basis, possibly because planting density did not vary as much as in previous studies where it varied by a factor of two or more.…”
Section: Source Of Variationcontrasting
confidence: 48%
“…In studies of openpollinated sunflowers in the absence of disease, yield in Manitoba was highest at spacings of 45 « 45 cm, or a population of about 50000 plants/ha (6). In Saskatchewan, yield at 25000 plants/ha was as good as at 75 000 plants/ ha, and between-row spac ings of 36,53, and 89 cm did not affect yield (10). In North Dakota, seed yield, test weight, and oil per centage of three oilseed hybrids and Teredovik' were not affected by populations of 36000, 48000, and 72000 plants/ha, and thus a population of 48000 plants/ha was recommended (5).…”
Section: Discussionmentioning
confidence: 87%
“…Because mycelial growth of Sclerotinia sclerotiorum in soil is limited to a few mm (II), it is evident that contact between host tissue and patho gen mycelium is brought about primarily by the actively growing root. Vijayalakshmi et al (10) found that roots of sunflower developed in the upper 13 cm soil layer in much greater amounts at a population level of 125 000 plants/ ha than at 25 000 plants/ha. On the other hand, sclerotia also become concentrated in the upper soil layers due to min imum disturbance of the soil in common field prac tices.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The harvest demonstrated a noteworthy resilience to dry season and the capacity to improve after times of high moisture stress. Populaces of 60,000 to 75,000 plants ha -1 at column spacing of 35 to 60 cm are prescribed for dry land creation [5]. The seed rates of sunflower going from 10.0 to 37.5 kg ha -1 .…”
mentioning
confidence: 99%